The Effect of Liquidity and Leverage to Return Shares with Profitability as an Intervening Variable in LQ45 Companies Listed on The Indonesia Stock Exchange (IDX) for the Period 2020 - 2024 - Herwadi, Dwi Juni Arti; Sutisna; Sari, Gema Ika (Amkop Management Accounting Review (AMAR), 2025)
This study aims to analyze the effect of Liquidity and Leverage on Stock Returns with Profitability as an intervening variable. The objects of the study were LQ45 Index companies listed on the Indonesia Stock Exchange (IDX) during the 2020– 2024 period. The method used was a quantitative approach with panel data regression analysis. The variables used included Liquidity (proxied by the Current Ratio) and Leverage (proxied by the Debt to Equity Ratio) as independent variables, Profitability (proxied by Return on Assets) as a mediating variable, and Stock Returns as the dependent variable. The results showed that Liquidity and Leverage had no significant effect on Stock Returns, while Profitability had a significant direct effect on Stock Returns. Furthermore, Liquidity had no significant effect on Profitability, but Leverage had a significant direct effect on Profitability. The mediation test using the Sobel test showed that Profitability did not significantly mediate the relationship between Liquidity and Stock Returns or between Leverage and Stock Returns. Management must prioritize strategies that can increase net profit and asset utilization efficiency. Increased profits will be directly reflected in share prices, benefiting investors and increasing stock returns.